Facilitation of holm oak recruitment through two contrasted shrubs species in Mediterranean grazed woodlands (Journal of Vegetation Science, 2012)
Question: Regeneration failure and gradual tree dieback are major threats for the persistence of savanna-like grazed oak woodlands. Current research has argued that the scarcity of ‘safe sites’, in particular shrubs, is the main cause of the lack of effective tree recruitment. But can different shrub species be considered as safe sites generally? Do two distinct shrub species, with contrasted life strategies, affect several life stages of tree regeneration in similar ways or do they speciﬁcally inﬂuence the recruitment process? Location: Holm oak woodlands of SW Iberian Peninsula (40°02′ N, 06°06′ W). Methods: We surveyed densities of recently emerged and surviving seedlings as well as small and large saplings over two consecutive years in 40 sites that were independently managed, comparing plots encroached by either Cistus ladanifer (a shallow-rooted shrub, forming dense populations, with reported allelopathic compounds) or Retama sphaerocarpa (a N2-ﬁxing, deep-rooted shrub that forms scattered populations) vs their respective control plots (without shrubs). To assess the effect of mature trees and both shrub species on the performance and survival of recently emerged oak seedlings, we established an acorn sowing experiment in the same surveyed microhabitats (open spaces, shrub, tree and tree–shrub). Results: The survey showed that both shrubs species had a positive effect at early recruitment stages. At later life stages, this effect weakened under Cistus whereas it strengthened under Retama. The acorn sowing experiment showed that both shrub species buffered abiotic conditions and enhanced seedling functioning similarly, but Retama enhanced seedling survival to a higher extent than Cistus. Conclusions: The two shrub species impose a speciﬁc template that is able to affect the long-term dynamics of Mediterranean oak woodlands. Cistus shrubs are effective in protecting seedlings physically against herbivores and facilitate early survival, but may compete with older stages of oak regeneration. In contrast, Retama shrubs exert stronger biological facilitation and guarantee longterm persistence of surviving seedlings. We argue that improved understanding of the effectiveness of different nurse plants and their contrasting factors is of major interest for the conservation and restoration of degraded oak woodlands

Belowground competition for nutrients in shrub-encroached Mediterranean dehesas (Nutrient Cycling in Agroecosystems, 2011)
Managing multilayered silvopastoral systems such as Mediterranean dehesas requires the study of nutrient resource partitioning among coexisting species and determination to what extent soil nutrients are limiting plant growth. We determined the effects of NPK fertilisation maintained over two consecutive years on dry matter production and nutritional status of pasture (herbaceous) species, two shrub species and Quercus ilex L. in two silvopastoral sites with different shrub-layer species. We selected two prominent Mediterranean shrub species that vary in their speciﬁc ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss, Retama site), and a dense shallow-rooting shrub (Cistus ladanifer L., Cistus site). Fertilisation signiﬁcantly (P B 0.05) increased pasture dry mass by 460% and 1,090% in the Retama and Cistus sites, respectively. Nitrogen uptake by pasture species was most stimulated in both sites, and was the major limiting nutrient for this group. At the Cistus site, fertilisation signiﬁcantly increased leaf dry mass of Q. ilex by 53%, but no signiﬁcant effect was found at the Retama site. There were no signiﬁcant effects of fertilisation treatments on dry mass and nutrient status of Retama cladodes and Cistus leaves. Vector analysis revealed that the magnitude of relative changes in nutrient uptake and dry matter production of pasture in response to fertilisation was markedly higher than that of Q. ilex, R. sphaerocarpa and C. ladanifer, suggesting high competitive ability of pasture species for soil nutrients. Results suggest that patterns of soil nutrient partitioning are site-speciﬁc and, thus, likely depend on the dominant species in the shrub layer

Shrub encroachment in Mediterranean silvopastoral systems: Retama sphaerocarpa and Cistus ladanifer induce contrasting effects on pasture and Quercus ilex production (Agriculture, Ecosystems & Environment, 2011)
Silvopastoral systems are threatened worldwide by progressive loss of either tree cover or herbaceous cover due to lack of tree regeneration and shrub encroachment, respectively. Grazed Mediterranean open woodlands, as Iberian dehesa, are an outstanding example of silvopastoral system where shrub encroachment has been proposed as an effective means to facilitate tree seedling recruitment and ensure the system persistence. Shrubs also may interact with pasture understorey and tree overstorey, thereby affecting the overall system productivity. We tested the effects of shrub encroachment on pasture yield, tree growth and acorn production in years of contrasting rainfall in Quercus ilex L. dehesas of centralwestern Spain.We compared the effects oftwo prominentMediterranean shrub species that differ in their ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss), and a dense shallow-rooting shrub (Cistus ladanifer L). In intermediate and dry years, pasture yield beneath tree canopy was lower by 21–35% than in open grassland. Pasture yield beneath tree canopy was not signiﬁcantly affected during the wet year. C. ladanifer encroachment signiﬁcantly reduced pasture yield by 68–98%, tree growth by 17–29%, and acorn yield by 6–44%. In contrast, R. sphaerocarpa signiﬁcantly increased pasture yield by 11–157% and tree growth by 6–13%, but had a neutral effect on acorn yield. Our results suggest that pasture is more sensitive to shrub encroachment and annual rainfall variation than is Q. ilex. The importance of C. ladanifer competition and R. sphaerocarpa facilitation on pasture yield increased in the driest year. We conclude that the sign and intensity of shrub encroachment effects on pasture and tree production in Mediterranean dehesas are species-speciﬁc and depend on temporal variation as a function of climate.